Fabrication, integration and reliability of nanocomposite based embedded capacitors in microelectronics packaging - Das, Rabindra N.; Lauffer, John M.; Markovich, Voya R. (Journal of materials chemistry, 2008)
We have developed a variety of barium titanate (BaTiO3)-epoxy polymer nanocomposite based thin film capacitors. In particular, we highlight recent developments on high capacitance, large area, thin film passives, their integration in printed wire board (PWB) substrates and the reliability of the embedded capacitors. A variety of nanocomposite thin films ranging from 2 microns to 25 microns thick were processed on PWB substrates by liquid coating or printing processes. SEM micrographs showed uniform particle distribution in the coatings. The electrical performance of composites was characterized by dielectric constant (Dk), capacitance and dissipation factor (loss) measurements. Nanocomposites provided high capacitance density (10-100 nF inch-2) and low loss (0.02-0.04) at 1 MHz. The manufacturability of these films and their reliability has been tested using large area (13 inch X 18 inch or 19.5 inch X 24 inch) test vehicles. Reliability of the test vehicles was ascertained by IR reflow, thermal cycling, pressure cooker test (PCT) and solder shock. Capacitors were stable after PCT and solder shock. Capacitance change was less than 5% after IR reflow (assembly) preconditioning (3X, 245 deg C) and 1400 cycles deep thermal cycle (DTC).